The Role of Political Communicators in Increasing Voter Participation in Pekanbaru City 2024 - Jupendri; Nurrahmi; Saidul Amin (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study to look how political communicators actually help raise voter turnout in the 2024 Pekanbaru regional election. Even tho direct elections already running for long time and info access is quite ok, the turnout still stuck low at 45.87%. Using qualitative approach inside a constructivist view, this research explore the roles of mayor candidates, political parties, the Election Commission KPU, and also voters in the whole communication process. The findings show that candidate pairs shape their messages and personal branding based on what they think community need, then share it through media they feel is more effective. Political parties give support by pushing the candidate image through community programs. KPU do outreach and voter education that try to suit voter characteristics. Voter turnout is influenced by various factors, including candidate personality, competence, vision and mission, program proposals, party support, past credibility, money politics, and the accessibility of polling stations. In general, turnout increases when political messages are delivered through appropriate media and supported by effective outreach from the Election Commission (KPU). These findings become a base for making better political communication strategy so public participation in regional elections can increase.